ANALISIS KINERJA SIMPANG EMPAT BERSINYAL JL. MAGELANG - SALAMAN MENGGUNAKAN SOFTWARE PTV VISSIM (Teras, 2023)
The intersection is one of the roads that is often the center of the problem of all traffic movements. To reduce conflicts at intersections, a traffic signaling device or APILL is needed, so it is called a signalized intersection. However, the existence of APILL does not rule out the possibility of causing congestion due to the imbalance of road conditions with the volume of existing vehicles. One of the signalized intersections experiencing traffic congestion is the Pakelan Intersection, Bulurejo District, Magelang Regency. So that a review is needed to improve the performance of the intersection using the traffic counting survey method and analysis using a comparison between MKJI 1997, PKJI 2014 and PTV Vissim 2022 Student Version software.The results of this study indicate that the peak hour traffic volume is at 06.30 - 07.30 WIB with 18,822 vehicles/hour. Calculations using the 1997 MKJI resulted in a volume of 6613.4 pcu/hour and the 2014 PKJI calculation of 5848.8 cur/hour. The average delay value is 75.66 and the degree of saturation is 0.78 with the level of service at the intersection is F. Therefore, the existing conditions need to be given alternative solutions to improve the performance of the intersection. There are two alternatives that are planned, namely: 1). Cycle time changes, 2). Direct left turn setting and route switching. From these two alternatives, the best alternative was obtained, namely setting a direct left turn and turning right on the south approach. From this alternative, the average delay value is 39.20, the degree of saturation is 0.662, and the level of service at the intersection is D. The alternative is generally safe but with a high degree of saturation, a review is needed to plan fly overs and underpasses which are expected to maximize intersection performance.Key words : Pakelan Magelang Signalized Intersection, MKJI 1997, PKJI 2014, and PTV Vissim software.